Characterization of Orgasmic Difficulties by Women: Focus Group Evaluation. (26th June 2013) - Kingsberg, Sheryl A.; Tkachenko, Natalia; Lucas, Johna; Burbrink, Amy; Kreppner, Wayne; Dickstein, Jodi B.
Abstract: Introduction. : Female orgasmic disorder (FOD) is the second most prevalent sexual disorder in women. According to the most recent revision of the Diagnostic and Statistical Manual of Mental Disorders, Fourth edition (DSM‐IV‐TR), the term "marked distress" is central to the diagnosis of FOD. In practice, the term "distress" for use as a criterion for a clinical diagnosis is a medical construct and may not correlate with the language used by women with FOD to describe what they are experiencing. Aim: The objective of this study was to explore the terminology used by women to describe their feeling associated with difficulties in achieving orgasm. Methods: Women experiencing difficulties in achieving orgasm were invited to participate in a focus group. The focus groups included a characterization, picture sort and language exploration exercise and completing the Female Sexual Distress Scale‐Desire, Arousal, Orgasm (FSDS‐DAO) to determine the impact and emotional associations of decreased/lack of orgasms. Main Outcome Measures: Patient reported terminology for characterization of their FOD, and validity of question 15 of FSDS‐DAO. Results: Sixty‐seven percent (44/66) of the women used the word "frustrated" when asked, "What one word would you use to describe your orgasm difficulties?" In the language exploration exercise, the most common term used to describe emotions associated with decreased orgasm was "frustration." Responses (0 = never to 4 = always) to question 15 (frustrated by problems with orgasm) of the FSDS‐DAO, ranged from 1 to 4 (mean 3.0) indicating that women were very frustrated. Conclusions: The term "frustrated" was the most relevant and common emotion women feel when they have difficulties in achieving orgasm. Additionally, the women consistently supported the content validity of question 15 of the FSDS‐DAO. Despite the use of the term "distress" in the DSM‐IV‐TR criteria for FOD, the term reflects the medical construct required to become a sexual dysfunction and does not appear to be an accurate representation of most women's feelings of orgasm difficulties.Kingsberg SA, Tkachenko N, Lucas J, Burbrink A, Kreppner W, and Dickstein JB. Characterization of orgasmic difficulties by women: Focus group evaluation. J Sex Med 2013;10:2242–2250.